Penentuan Garis Sempadan Sungai dan Irigasi di Wilayah Ibukota Kabupaten Lampung Tengah - Mukhlis, Muhammad; Kustiani, Ika; Widyawati, Ratna (Jurnal Profesi Insinyur Universitas Lampung, 2021)
In order to preserve, reassure, maintain and sustainablity of water, water sources and structures, it is necessary to efforts and restraint the water's destruction their sources and the surrounding area. Border Line is the outer safety boundary line that is determined structures and / or border drawn at a parallel to the road median, the outside edge of the bridge head, river bank, channel edge, embankment, edge of the swamp, edge of reservoir, edge of spring , railway tracks, electric power lines and gas pipes, depending on the type of border line listed. On the outside of this line, landowners are not allowed to build buildings. Nowadays, especially in the area of ​​ Lampung Tengah Regency, there are many violations of this border line, both on the river border and irrigation border line. To anticipate this continuing situation, before constructing a building and applying for a building permit, landowners must know the various lines that are on the land they own. The control can be carried out in stages starting from giving a warning letter to this violation and providing an opportunity to correct before the last warning comes, which is then followed by an act of forced demolition.